THE ISSUE OF ESTABLISHING A CREDIT SYSTEM IN THE TURKESTAN REGION (BASED ON THE MATERIALS OF THE TURKESTAN COLLECTION) - Исмоилова Парвина Хамиджон кизи (TARIXIY TADQIQOTLAR, 2026)
The study examines the problem of the formation of a credit system in the Turkestan region in the second half of the nineteenth and the early twentieth centuries. The research is based on materials from the pre-revolutionary publication Turkestan Collection, which make it possible to trace the process of establishing credit institutions in the region and to identify the specific features of their functioning. Special attention is paid to analyzing how the local population perceived the credit system, the reasons for its establishment, as well as the economic and administrative prerequisites for its creation. In addition, the article explores the role of partnerships and other forms of associations in the development of credit relations, as well as their importance for supporting trade, agriculture, and the overall economic